Effect of neem ( A. Juss) insecticides on parasitoids Azadirachta indica A .Juss) insecticidesonparasitoids - Cóndor Golec, Aníbal F. (2007)
Azadirachta indica A. Juss (Meliaceae) is an indian tree, commonly called the neem tree. It has many useful compounds that act as insecticide. Neem insecticides have in their composi-tion azadirachtin, a tetranortriterpenoid plant limonoid which can be isolated from the seeds of the neem tree(Mordue & Blackwell, 1993). Azadirachtin is also termed Azadirachtin A (Rembold, 1989).